Fomenters of Fiasco: Explaining the Failed Policy Response to COVID-19 in the United States - Lawrence D. Brown (International Review of Public Policy)
Policy responses to COVID-19 in the United States have been constrained by electoral calculi that run from the executive to the legislative branch of the central government and thence also to the federal bureaucracy and the states. The policy outcomes are as disappointing for US democracy as they are for the health of the US population.